A transposon‐introduced G‐quadruplex motif is selectively retained and constrained to downregulate CYP321A1. (5th April 2022) - Deng, Zhongyuan; Zhang, Yuting; Gao, Chao; Shen, Wei; Wang, Shan; Ni, Xinzhi; Liu, Sisi; Li, Xianchun
Abstract: Insects utilize xenobiotic compounds to up‐ and downregulate cytochrome P450 monooxygenases (P450s) involved in detoxification of toxic xenobiotics including phytochemicals and pesticides. G‐quadruplexes (G4)‐forming DNA motifs are enriched in the promoter regions of transcription factors and function as cis ‐acting elements to regulate these genes. Whether and how P450s gain and keep G4 DNA motifs to regulate their expression still remain unexplored. Here, we show that CYP321A1, a xenobiotic‐metabolizing P450 from Helicoverpa zea, a polyphagous insect of economic importance, has acquired and preserved a G4 DNA motif by selectively retaining a transposon known as HzIS1‐3 that carries this G4 DNA motif in its promoter region. The HzIS1‐3 G4 DNA motif acts as a silencer to suppress the constitutive and induced expression of CYP321A1 by plant allelochemicals flavone and xanthotoxin through folding into an intramolecular parallel or hybrid‐1 conformation in the absence or presence of K + . The G4 ligand N ‐methylmesoporphyrin IX (NMM) strengthens the silencing effect of HzIS1‐3 G4 DNA motif by switching its structure from hybrid‐1 to hybrid‐2. The enrichment of transposons in P450s and other environment‐adaptation genes implies that selective retention of G4 DNA motif‐carrying transposons may be the main evolutionary route for these genes to obtain G4 DNA motifs. Abstract : CYP321A1, a xenobiotic‐metabolizing P450 from Helicoverpa zea, a polyphagous insect of economic importance, has acquired and preserved a G4 DNA motif by selectively retaining a transposon known as HzIS1‐3 that carries this G4 DNA motif in its promoter region. The HzIS1‐3 G4 DNA motif acts as a silencer to suppress the constitutive and induced expression of CYP321A1 by plant allelochemicals flavone and xanthotoxin. This represents to our knowledge not only the first characterized silencer for down‐regulation of insect P450s, but also the first discovery of acquisition of G4 DNA motifs by non‐transcription factor genes via selective retention of G4 DNA motif‐carrying transposons.